Development Of A Beginning Reading Program For Slow Learners With Montessori Techniques - Janah, Rahmatul; Aprilia, Imas Diana (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Reading is the basis for mastering various fields of study. Slow learners generally fail to understand basic lessons and concepts in academics, such as reading, writing, mathematics and language. This is because the above processes require a fairly complicated cognition process. So in overcoming obstacles to learning to read at the beginning of slow learners, a reading technique is needed that suits the needs of children. One of the reading techniques that can be used is the Montessori technique which is based on the Montessori method.The objectives of this study are as follows: (1) Knowing the stages of the process of developing an initial reading program for slow learners with Montessori techniques (2) Knowing the feasibility of developing an initial reading program for slow learners with Montessori techniques. The research method used in this study is a mixed research method. The final product of this study resulted in a beginning reading learning program with Montessori techniques consisting of products: (1) initial reading identification and assessment format (2) Learning program plan (3) Guidebook for teachers (4) Student worksheets (5) Module on Montessori reading techniques that have been modified for slow learner children. Based on research findings, data analysis and theoretical discussion, it can be concluded that the application of the beginning reading program in slow learners with Montessori techniques is feasible because it suits the needs of children and is able to improve initial reading skills. This program also helps teachers to know the stages of making individual learning programs for students with special needs.